Incorporation of Water Hyacinth, Eichhornia crassipes Meal in Aqua-feed and its Efficacy on Growth Performance of roho labeo, Labeo rohita (Hamilton, 1822) Reared in Cagev - Md. Al-Amin Sarker; Kamrun Nahar; Hasna Banu; Turjaun Nesa (International Journal of Aquaculture and Fishery Sciences - Peertechz Publications, 2020)
The major challenge of fish production is to develop high quality low cost fish feed which indicates the importance of low cost aquaculture technology. This study was conducted to Incorporation of water hyacinth, Eichhornia crassipes meal in aqua-feed and its efficacy on growth and nutritional aspects of roho labeo, Labeo rohita (Hamilton, 1822) reared in cage during March to May, 2018. Feed formulation was performed with water hyacinth considering the nutritional balance of the feed. roho labeo were fed with control T1 feed (0% water hyacinth based WH 0 feed), 15% water hyacinth meal based feed T2 feed and 25% water hyacinth meal enriched feed T3 feed at the feeding level of 4% body weight for 12 weeks (twelve weeks) in experimental cages (each treatment with 3 replications) at Isamoti river, Santhia, Pabna, Bangladesh. The food conversion ratio (FCR) value was significantly lower in fish group fed with T1 feed (3.0±0.01) and T2 feed (3.0±0.03) than T3 feed (3.5±0.04).The average specific growth rates (SGR) was (1.11±0.00), (1.11±0.01) and (0.95±0.01) (%,bwd-1, body weight per day) in treatment T1, T2 and T3 respectively. The SGR was significantly (P<0.05) higher in fish group fed with T1 feed (1.11±0.00) and T2 feed (1.11±0.01) than T3 feed (0.95±0.01) (%,bwd-1). The production (kg/cage/cycle) of Labeo rohita was (40.41±.19)T1, (40.49±.21)T2, (35.93±.07) T3 respectively. The production did not differ significantly between T1 and T2. Significantly higher cost benefit analysis (CBR) was found with T2 (0.68±.02) and lower was found with T1 (0.61±.01) and T3 (0.57±.01). The cost of feed production decreases as the incorporation levels of water hyacinth increases.